The touch of individuals with visual impairments to geometry: Tactile materials vs origami - Fatma Nur Aktaş (Journal of Pedagogical Research, 2024)
This study aims to examine the roles of tactile materials and origami models in the perception of concept definitions and representations in geometry applications of individuals with visual impairments. This case study draws on data from eight individuals with visual impairments selected according to the purposive sampling method in a mathematics village. Video recordings of focus group interviews conducted with tactile materials and origami models were analyzed by content analysis. Tactile materials made it possible for them to perceive concept definitions and visual representations, while the construction of origami models made every component designable, such as the relationship between concepts, visual prototypes and sub-concepts. Individuals with visual impairments have been quite successful in designing different representations and strategies for geometric concepts with perfect folding. Thus, it has been determined that origami is an accessible material for individuals with visual impairments to do geometry with creases and models.